THE ROLE OF ENTREPRENEURIAL MINDSET IN MANAGEMENT AND SME GROWTH - Abdukhafizova Madinabonu Mirabbas qizi (Modern American Journals, 2025)
Small and medium-sized businesses (SMEs) are essential to economic expansion, their performance frequently hinges more on the attitudes of its management than on the resources within their control. This study looks at how management and the expansion of SMEs are affected by entrepreneurial mindset. It makes the case that mindset is a managerial tool rather than just a characteristic of entrepreneurs. In order to provide a theoretical framework, the study uses a conceptual research method, combining knowledge from organizational, management, and entrepreneurship theories. The framework, which is based on the resource-based and a flexible capacity perspective, presents an entrepreneurial mentality as a managerial philosophy, a dynamic capability, or a cognitive asset. Three main ways that an entrepreneurial mindset aids in the expansion of SMEs are highlighted in the discussion: opportunity-oriented decision-making, creative management techniques, and crisis-resilience. Employee empowerment, agility, and competitiveness are all enhanced when an entrepreneurial spirit is ingrained in company culture. According to the findings, SME managers that deal with uncertain situations and limited resources must develop an entrepreneurial mindset. Beyond its scholarly value, the study has applications for leaders, legislators, and educators: education and support for SMEs ought to emphasize the growth of entrepreneurial mindsets in addition to technical proficiency. In order to better understand how SMEs can attain sustainable growth in dynamic marketplaces, the article reframes the entrepreneurial mindset as a bridge between management and entrepreneurship.
Keywords: Management, small and medium-sized enterprises (SMEs), Innovation, Resilience, Opportunity recognition and SME growth.